5-fluorouracil and folinic acid-induced mucositis: no effect of oral glutamine supplementation. - Jebb, SA; Osborne, R; Maughan, T; Mohideen, N; Mack, P; Mort, D; Shelley, MD; Elia, M (1994)
In some clinical situations the endogenous production of glutamine may be insufficient to maintain optimal tissue structure and function such that glutamine becomes a conditionally essential amino acid. Studies in laboratory animals have demonstrated that glutamine supplementation can reduce the incidence and severity of cytotoxic-induced mucositis. This study examined the role of oral glutamine supplementation in the management of mucositis caused by 5-fluorouracil (5-FU) and folinic acid. Twenty-eight patients with gastrointestinal cancers were randomised to receive 16 g of glutamine per day for 8 days, or placebo, in a randomised double-blind trial before crossing over to the alternative supplement during the second treatment cycle. The supplement was well tolerated with no apparent adverse effects, but failed to have any significant effect on oral mucositis assessed by the patients or investigator. The possible reasons for this apparent lack of benefit are discussed.